A PROTOTYPE OF TRUE DAWN OBSERVATION AUTOMATION SYSTEM - M Basthoni (Jurnal Sains Dirgantara, 2020)
It requires adequate true dawn observation data both in quality and quantity to correct or verify the accuracy of the early true dawn criteria set by the Ministry of Religion of Republic of Indonesia, which in the last decade had been doubted by several parties. However, temperature and unfavorable field conditions present challenges in observing the true dawn. This paper describes the development of the True Dawn Observation Automation System which includes hardware and software requirements, system installation and performance testing in three locations: Karimunjawa (-5.78S, 110.48E, 1 m above sea level), Banyuwangi (-7.97S, 114.42E, 1 m above sea level) and Semarang (-6.97S, 110.29E, 15 m above sea level). An analysis of the data is also presented in this paper which includes the variability due to moonlight and light pollution on true dawn detection. The test results show that the system is running well but it needs upgraded GPS and Real Time Clock module so the system can work better. Meanwhile, analysis of the data recorded by the system shows that moonlight has a strong effect on true dawn detection in locations with low light pollution (Banyuwangi and Karimunjawa), an average difference of around 3.4° (13.6 minutes) compared to when moonlight was absent. Meanwhile, in areas with high light pollution (Semarang) it does not have a significant effect, an average difference of around 0.25° (1 minute). This study also proposes that true dawn is detected when the Sun's position averages -20 ± 0.2 degrees below the horizon.